Co-Delivery of Paclitaxel Prodrug, Gemcitabine and Porphine by Micelles for Pancreatic Cancer Treatment via Chemo-Photodynamic Combination Therapy - Wu Qiwei; Ma Xiaodong; Zhou Wenhui; Yu Rong; Rosenholm Jessica M; Tian Weizhong; Zhang Lirong; Wang Dongqing; Zhang Hongbo (MDPI, 2022)
Pancreatic carcinoma is an aggressive subtype of cancer with poor prognosis, known for its refractory nature. To address this challenge, we have established a stable nanoplatform that combines chemotherapy with photodynamic therapy (PDT) to achieve better curative efficacy. First, we designed and synthesized a disulfide-bonded paclitaxel (PTX)-based prodrug, which was further mixed with gemcitabine (GEM) and photosensitizer THPP in an optimized ratio. Subsequently, the mixture was added dropwise into amphiphilic polymer DSPE-PEG water solution to form micelles composed of DSPE-PEG nanoparticles (TPG NPs). The TPG NPs were around 135 nm, and showed great ability of DTT stimulated release of PTX and GEM. Moreover, the TPG NPs can be efficiently uptaken by pancreatic cancer PANC-1 cells and effectively kill them, especially when combined with 650 nm laser irradiation. Finally, the TPG NPs have shown enhanced long-term circulation ability and also exhibited efficient anti-tumor activity in combination with 650 nm laser irradiation in a pancreatic cancer mouse model. In summary, the designed TPG NPs possesses great potential for co-delivery of paclitaxel prodrug, GEM and THPP, which enables combined chemo-photodynamic therapy for cancer treatment. In addition, the stimulated release of PTX prodrug and GEM also allows for better targeting of tumor cells and the increased therapeutic effect against cancer cells. Overall, the TPG NPs can serve as a good candidate for pancreatic cancer treatment.